Fiddling in Euroland as the global meltdown nears - Dimitri B. Papadimitriou; L. Randall Wray (Levy Economics Institute of Bard College, 2012)
President Dimitri B. Papadimitriou and Senior Scholar L. Randall Wray argue that the common diagnosis of a "sovereign debt crisis" ignores the crucial role of rising private debt loads and the significance of current account imbalances within the eurozone. Profligate spending in the periphery is not at the root of the problem. Moreover, pushing austerity in the periphery while ignoring the imbalances within the eurozone is a recipe for deflationary disaster. The various rescue packages on offer for Greece will not ultimately solve the problem, say the authors, and a default is a very real possibility. If a new approach is not embraced, we are likely seeing the end of the European Monetary Union (EMU) as it currently stands. The consequences of a breakup would ripple throughout the EMU as well as the shaky US financial system, and could ultimately trigger the next global financial crisis.
Keywords: 330